2016
DOI: 10.1002/phar.1770
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Alcohol Withdrawal Syndrome in Critically Ill Patients

Abstract: Approximately 16-31% of patients in the intensive care unit (ICU) have an alcohol use disorder and are at risk for developing alcohol withdrawal syndrome (AWS). Patients admitted to the ICU with AWS have an increased hospital and ICU length of stay, longer duration of mechanical ventilation, higher costs, and increased mortality compared with those admitted without an alcohol-related disorder. Despite the high prevalence of AWS among ICU patients, no guidelines for the recognition or management of AWS or delir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 43 publications
(186 reference statements)
1
53
0
13
Order By: Relevance
“…Currently, the standard of care for alcohol withdrawal centers on benzodiazepine therapy until cessation of alcohol withdrawal symptoms occurs or additional pharmacological therapy is needed. 1 , 2 The choice of additional therapy, however, is not standardized nor are there well-established regimens in place. 1 This is particularly important for high-risk patients such as those who have a personal or family history of alcohol withdrawal or DT.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the standard of care for alcohol withdrawal centers on benzodiazepine therapy until cessation of alcohol withdrawal symptoms occurs or additional pharmacological therapy is needed. 1 , 2 The choice of additional therapy, however, is not standardized nor are there well-established regimens in place. 1 This is particularly important for high-risk patients such as those who have a personal or family history of alcohol withdrawal or DT.…”
Section: Discussionmentioning
confidence: 99%
“…bFGF can promote the regeneration of peripheral nerves. However, previous studies [5][6][7][8][9][10][11] did not analyze the viscoelastic reduction, dull/drowsy body, significantly increased sleep time, body weight growth, and less eating than group CON, proving the successful establishment of the CAI rat model. Electrophysiological test: Alcoholism in humans or animals always resulted in damage to the peripheral nerves.…”
Section: ■ Introductionmentioning
confidence: 88%
“…Chronic alcohol intoxication (CAI)-induced peripheral neuropathy was discovered earlier, but caught people's attention only towards the end of the 19th century 4 . Many scholars have conducted research on drug therapies against CAI 5,6 . Monforte et al 7 showed that long-term intake of ethanol can cause changes in the cytoskeletal structure of peripheral nerves, and affect the transportation among the axons, thus affecting the functional integration of neurons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[69][70][71][72] Other studies, however, have demonstrated that propofol is associated with longer hospital stays, and the significant risks of hypotension and respiratory depression associated with this medication necessitate mechanical ventilation and close monitoring in the ICU. 71,73,74 Ketamine is another NMDA-antagonist with less potential for respiratory depression. Two small retrospective studies found that the use of ketamine as an adjunct reduced benzodiazepine requirements in patients with RAW.…”
Section: Adjunctive Medicationsmentioning
confidence: 99%